Pengujian Kualitas Perangkat Lunak Website Jurusan Teknologi Informasi Politeknik Negeri Jember Menggunakan ISO 9126 - Maulidatul Muauwanah; Irsyad Romadloni; Muhammad Abdul Muqid; Muhammad Hasyim Al Arif; Rani Purbaningtyas (Jurnal Teknik Informatika dan Teknologi Informasi, 2023)
In the rapidly developing digital era, websites have become the main tool in disseminating information and facilitating interaction, including in the world of education. Jember State Polytechnic has an Information Technology Department with a variety of study programs. However, to meet the needs of students and stakeholders, the quality of the Information Technology Department website must be high. Website quality affects user experience, information understanding, and institutional image. This quality evaluation will encourage website maintenance and improvement in order to continue to provide the best benefits for users in the Information Technology Department of Jember State Polytechnic.This research uses an evaluation method based on ISO 9126 standards to measure and improve the quality of the Information Technology Department website. This standard covers various aspects of quality such as functionality, reliability, usability, efficiency, maintainability, and portability. The evaluation results show that this website meets the standards well, with an overall quality level of 92.2%. It provides guidance for website developers to improve services to stay effective and relevant.